Jenis-Jenis Jamur Makroskopis di Hutan Hujan Mas Desa Kawat Kecamatan Tayan Hilir Kabupaten Sanggau - Masnur Turnip, Kiki Anggraini, Siti Khotimah, (Universitas Tanjungpura, 2015)
Macroscopic fungi have a very important role for the ecosystem of the forest and human life. This research aimed to find out the types of macroscopic fungi found in the Hujan Mas Forest, Kawat Village, Tayan Hilir Sub-district, Sanggau Regency. The research was conducted carried out for three mounth from May to August 2015 using the cruise method. The research findings showed that there were 26 species of macroscopic fungi consisting of 5 orders and 13 families. The most commonly found fungi were from Order Aphylloporales with 17 types, followed by the Order Agaricales with 6 types and the OrderPezizales, Order Xylariales and Order Polyporales each with 1 type respectively. The macroscopic fungi found in the Hujan Mas Forest, Kawat Village, Tayan Hilir Sub-district grew mostly on the dead tree substrate.